The impact of silica diagenesis on organic-rich carbonate source rocks: a review - Abu-Mahfouz, Israa S. (Frontiers in Earth Science, 2025)
Silica diagenesis plays a critical yet understudied role in modifying the hydrocarbon potential of organic-rich carbonate source rocks. This review systematically examines how silica transformations—from biogenic opal to quartz—fundamentally alter rock properties through three key mechanisms: First, mineralogical reorganization, where silica dissolution creates secondary porosity while cementation occludes pore throats, directly impacting fluid flow pathways. Second, geochemical feedbacks, including pH-driven carbonate dissolution and catalytic effects on organic matter maturation that influence hydrocarbon generation kinetics. Third, pore network evolution, where silica-induced microfractures provide migration conduits but heterogeneous cementation can trap hydrocarbons. The synthesis highlights three novel insights: (1) The timing of silica diagenesis relative to hydrocarbon generation determines whether pores remain open for migration or become sealed; (2) Microscale silica-carbonate interactions control reservoir quality more significantly than previously recognized; and (3) Modern analytical techniques reveal complex diagenetic histories that challenge traditional models. By integrating petrographic, geochemical, and petrophysical evidence, this work establishes a predictive framework for evaluating how silica diagenesis impacts petroleum systems, from source rock maturation to trap integrity. The findings are particularly relevant for unconventional carbonate reservoirs, where subtle diagenetic modifications disproportionately affect producibility. This comprehensive analysis advances our capacity to interpret reservoir behavior and optimize exploration strategies in silica-rich sedimentary basins worldwide.